Impact of multifactorial interventions with medication and lifestyle optimization on patients with type 2 diabetes: A randomised controlled trial - Marwan El-Deyarbi; Luai Ahmed; Jeffrey King; Zelal S. Adi; Ahmed Al Juboori; Nirmin A. Mansour; Huda Al Nuaimi; Rami Beiram; Salahdein Aburuz (PLoS ONE, 2025)
Background Clinical evidence on the protective effects of a balanced diet, exercise, and medication adherence along with intensive glucose-lowering therapies on diabetes progression is lacking, and interventions that are most effective in slowing cardiorenal metabolic complications in patients with diabetes remain unelucidated. Objective To determine the effects of long-term multifactorial interventions on clinical outcomes in Emirati patients with diabetes attending ambulatory healthcare clinics. Methods We conducted a randomised controlled clinical trial at the Oud Al-Touba Clinic involving 192 participants with diabetes, who were blinded to the intervention and control groups, and followed up for 1 year. At the 3-, 6-, and 9-month visits, the intervention and control groups received multifactorial interventions and standard routine care, respectively. Glycated haemoglobin A1c (HbA1c) levels, estimated glomerular filtration rate (eGFR), blood pressure, electrolyte levels, and cardiovascular events were assessed at study completion. Results During a mean follow-up of 11.9 months, 40.4% of the participants in the intervention group (31.6% in the control group) achieved diabetes control (HbA1c < 7%), with a significant mean difference of −0.36% in HbA1c levels between the groups (95% CI: −0.54 – −0.19, P < 0.01). Participants in the multifactorial group achieved a significant mean difference in low-density lipoprotein cholesterol levels (mean difference = −0.14, 95% CI: −0.27–0.001, P < 0.03), and significant adjusted mean difference of eGFR levels difference (3.93 mL/min/1.73 m2, 95% CI: 1.27–6.58, P < 0.01) at study completion compared to those in the control group. Moreover, the percentage of participants in the intervention group who met the blood pressure target increased from 38.3% to 51.1%, accompanied with a decrease in serum electrolyte levels, compared to 34.7% to 36.7% in the control group at the end of the follow-up. Conclusions Implementing multifactorial interventions by a multidisciplinary team improved several clinical manifestations, including HbA1c, SBP, and eGFR, and decreased cardiovascular risk factors despite the decreased diabetes medication use. Trial registration ClinicalTrials.gov NCT04942119